2014
DOI: 10.1109/tdei.2013.003466
|View full text |Cite
|
Sign up to set email alerts
|

Understanding electrical discharge endurance of epoxy micro- and nano-composites through thermal analysis

Abstract: Thermal analysis of epoxy solid dielectrics containing micron sized, nanometer sized, and a mixture of the two sizes, of silica was performed. Measurements of thermal conductivity and thermo gravimetric analysis (TGA) were conducted. The TGA data showed higher weight loss initiation temperatures for samples containing up to 5% by weight of nanofillers as compared to the same material with much higher levels of conventional microfillers and unfilled sample, and this was in good correlation with the erosion dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[94] The linear and nonlinear rheological property of filled polymers can be characterized in order to make it possible to scan in frequency and in deformation a wide enough range to understand the properties of the mixtures and to link them to the dispersion, to the interactions and to the structure of the studied mixture. [95,96] The structure of semidilute suspensions of single-walled carbon nanotubes in polymeric matrices in the works of Chatterje and Krishnamoorti [97] indicates an aggregate presence in the polymer matrix that becomes slightly denser with increasing nanotube concentration. At low filler content, the fillers are separated in the mixture.…”
Section: Determination Of Percolation Thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…[94] The linear and nonlinear rheological property of filled polymers can be characterized in order to make it possible to scan in frequency and in deformation a wide enough range to understand the properties of the mixtures and to link them to the dispersion, to the interactions and to the structure of the studied mixture. [95,96] The structure of semidilute suspensions of single-walled carbon nanotubes in polymeric matrices in the works of Chatterje and Krishnamoorti [97] indicates an aggregate presence in the polymer matrix that becomes slightly denser with increasing nanotube concentration. At low filler content, the fillers are separated in the mixture.…”
Section: Determination Of Percolation Thresholdmentioning
confidence: 99%
“…The linear and nonlinear rheological property of filled polymers can be characterized in order to make it possible to scan in frequency and in deformation a wide enough range to understand the properties of the mixtures and to link them to the dispersion, to the interactions and to the structure of the studied mixture. [ 95,96 ]…”
Section: Rheology Of Filled Systemsmentioning
confidence: 99%
“…Castellon [17] thought that nano-silica could improve the space charge distributions of epoxy hybrid composites. Iyer [18] reported that micronano titania can improve the thermal stability of epoxy hybrid composites. Couderc [19] found that the addition of quartz and montmorillonite increased the glass transition temperature of EP.…”
Section: Introductionmentioning
confidence: 99%